2015
DOI: 10.1148/radiol.14140876
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Multidetector CT for the Characterization of Incidental Adrenal Nodules: Diagnostic Performance of Contrast-enhanced Material Density Analysis

Abstract: Contrast-enhanced dual-energy multidetector CT with material density analysis allows differentiation between adrenal adenomas and nonadenomas, reflecting an improved ability over nonenhanced multidetector CT for diagnosis of lipid-poor adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 33 publications
2
34
1
Order By: Relevance
“…Dual-energy computed tomography (DECT) has been used clinically in a variety of applications, such as kidney stone characterization, 1,2 the diagnosis of gout, 3 and the characterization of renal and adrenal lesions. 4,5 Additionally, it provides a pathway to new display and postprocessing techniques that can aid and expedite diagnosis, such as automatic bone removal 6 and virtual noncontrast imaging. 7,8 Another visualization technique possible with DECT is virtual monoenergetic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy computed tomography (DECT) has been used clinically in a variety of applications, such as kidney stone characterization, 1,2 the diagnosis of gout, 3 and the characterization of renal and adrenal lesions. 4,5 Additionally, it provides a pathway to new display and postprocessing techniques that can aid and expedite diagnosis, such as automatic bone removal 6 and virtual noncontrast imaging. 7,8 Another visualization technique possible with DECT is virtual monoenergetic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…For adrenal masses >1 cm, the specificity for characterizing a lesion as benign was 100% in a small series of 42 patients with 51 adrenal masses, but subsequent studies have shown slightly lower specificity. However, the use of dual energy CT has not become mainstream due to limited use of dual energy scanners for this purpose worldwide [12][13][14][15].…”
Section: Min a Ast´1 00mentioning
confidence: 99%
“…Examples include incidental detection of an adrenal lesion. Such a lesion can be characterized using virtual unenhanced images: if the attenuation of the lesion is significantly low, a diagnosis of lipid-rich adenoma can be made without the need for additional imaging (28,29). Similarly, complex lesions in kidneys, which have high attenuation on conventional arterial phase images, can be further evaluated by using virtual unenhanced images and iodine map (30).…”
Section: Incidental Lesion Characterizationmentioning
confidence: 99%
“…As with other DECT technologies, the opportunity exists for reducing contrast load with SDCT and exploiting the higher attenuation of iodine at lower energies (5,(14)(15)(16)(17). This has (27) Incidental lesion characterization Characterization of incidental nodules, and masses, particularly in Virtual unenhanced, iodine map kidneys, adrenals and lungs (28) CT, computed tomography; CTA, CT angiography; TAVI, transcatheter aortic valve implantation.…”
Section: Impact On Contrast Dose and Radiation Dosementioning
confidence: 99%